2016
DOI: 10.1177/2333794x16645699
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Oxygenation in Severe Acute Respiratory Distress Syndrome With High-Volume Continuous Veno-venous Hemofiltration

Abstract: The efficacy and therapeutic mechanisms of continuous renal replacement therapy (CRRT) for improvement of oxygenation in acute respiratory distress syndrome (ARDS) remain controversial. These questions were addressed by retrospective analysis of severe ARDS patients admitted to the pediatric intensive care unit of our hospital from 2009 to 2015 who received high-volume continuous veno-venous hemofiltration during mechanical ventilation. There was a significant improvement in partial oxygen pressure/fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…CRRT, one of extracorporeal treatments, has been used for critically ill patients with or without AKI or acute kidney failure and ARDS is one of nonrenal indications for CRRT [11]. Studies showed that CRRT brought benefits to ARDS patients (non-AKI), including improvement of oxygenation and survival [14, 25]. We used CVVH, one of CRRT, in the current study and we found significant improvement of EVLWI in both groups after initiation of treatment.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…CRRT, one of extracorporeal treatments, has been used for critically ill patients with or without AKI or acute kidney failure and ARDS is one of nonrenal indications for CRRT [11]. Studies showed that CRRT brought benefits to ARDS patients (non-AKI), including improvement of oxygenation and survival [14, 25]. We used CVVH, one of CRRT, in the current study and we found significant improvement of EVLWI in both groups after initiation of treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Recent clinical and animal studies showed that CVVH was associated with improved oxygenation and organ function, facilitated fluid removal, and decreased EVLW in ALI/ARDS patients [25, 28]. Many cytokines and biomarkers, including endothelial and epithelial alveolar biomarkers, involved in the pathogenesis of ARDS and sepsis are released and it is believed that CVVH attenuates the entire inflammatory response and reduces the levels of biomarkers via removal of cytokines [14, 36]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results do not confirm some of the previous findings suggesting that early RRT was associated with favorable outcomes in critically ill patients. 1,10,11 One of the reasons for this discrepancy could be because the initiation of RRT in those studies occurred within a few hours of admission to the ICU. Interestingly, our survival analysis showed a trend toward a survival benefit for patients with RRT initiation after >48 hours but was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%